1997
DOI: 10.1084/jem.185.10.1859
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of  T Cell Receptor (TCR)–CD3-ζ Complexes after Antigenic Stimulation

Abstract: T cell activation by specific antigen results in a rapid and long-lasting downregulation of triggered T cell receptors (TCRs). In this work, we investigated the fate of downregulated TCR– CD3-ζ complexes. T cells stimulated by peptide-pulsed antigen-presenting cells (APCs) undergo an antigen dose-dependent decrease of the total cellular content of TCR-β, CD3-ε, and ζ chains, as detected by FACS® analysis on fixed and permeabilized T–APC conjugates and by Western blot analysis on cell lysates. The time course o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

24
239
2

Year Published

1998
1998
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 283 publications
(265 citation statements)
references
References 19 publications
(34 reference statements)
24
239
2
Order By: Relevance
“…Downregulation of z expression has been reported in T and NK cells of patients with cancers (Zea et al, 1995;Rabinowich et al, 1996Rabinowich et al, , 1998Reichert et al, 1998a, b;Kiessling et al, 1999;Kuss et al, 1999;Whiteside, 1999Meidenbauer et al, 2002;Reichert et al, 2002) and with chronic infections, including HIV (Stefanova et al, 1996;Zea et al, 1998). A transient loss of z expression appears to be a normal consequence of signalling via TcR (Valiutti et al, 1997). However, in patients with cancer or chronic infections such as leprosy or HIV, z expression may never recover to equal that in normal T cells (Stefanova et al, 1996;Zea et al, 1998), and its absence or partial loss in cancer patients appears to be substantially more common in tumour-infiltrating than in circulating T lymphocytes (Otsuji et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Downregulation of z expression has been reported in T and NK cells of patients with cancers (Zea et al, 1995;Rabinowich et al, 1996Rabinowich et al, , 1998Reichert et al, 1998a, b;Kiessling et al, 1999;Kuss et al, 1999;Whiteside, 1999Meidenbauer et al, 2002;Reichert et al, 2002) and with chronic infections, including HIV (Stefanova et al, 1996;Zea et al, 1998). A transient loss of z expression appears to be a normal consequence of signalling via TcR (Valiutti et al, 1997). However, in patients with cancer or chronic infections such as leprosy or HIV, z expression may never recover to equal that in normal T cells (Stefanova et al, 1996;Zea et al, 1998), and its absence or partial loss in cancer patients appears to be substantially more common in tumour-infiltrating than in circulating T lymphocytes (Otsuji et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…18 In an earlier report on native TCR/CD3 complex functions we showed that individual human CTLs serially use sets of TCR/CD3 complexes to engage target TAA and that following signal transduction the disengaged TCR/CD3 complexes become inactivated and degraded. 8,9 Prior unengaged TCRs on the same T lymphocyte can engage with antigens on new target cells. We proposed that this serial use of sets of TCRs may underlie the ability of individual CTL to serially lyse multiple target cells.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 We and others showed that the level of activation of a T lymphocyte function, eg cytolysis, is positively correlated with the amount of bsmAb crosslinking TCRs and activation/target antigens, [5][6][7] and that following TCR/CD3 complex engagement with these antigens, TCRs on a single CTL that were triggered, become inactivated and degraded. 8,9 Hence, CTLs serially use sets of TCR/CD3 complex for antigen engagement redirected T lymphocyte mediated tumor cell lysis, as well as lymphokine production were determined using RCC lines as target/stimulator cells, which express either no or increasing densities of the TAA. A functional and dynamic balance between ch-Rec densities on cytotoxic T lymphocytes (CTLs) on the one hand and TAA densities on RCCs on the other, was found.…”
Section: Introductionmentioning
confidence: 99%
“…Engagement of the TCR leads not only to activation of T cells, but also to internalization and lysosomal degradation of the receptor complex [1]. The latter process serves to terminate signaling, and has been shown to be dependent on the tyrosine kinase activity of Lck [2,3] and ubiquitination by c-Cbl [4][5][6].…”
Section: Introductionmentioning
confidence: 99%